Metabolic Alterations in Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Alterations in regional cerebral metabolism have been demonstrated by in vivo proton magnetic resonance spectroscopy of 8 children (7 - 16 years) with established multiple sclerosis at the Max-Planck-Institut fur biophysikalische Chemie, Postfach, and Abt.